E- COURT OF FIRST INSTANCE OR ELECTRONIC WRIT-OF-PAYMENT PROCEDURE (EPU) - Gołuc, Marta (Człowiek w cyberprzestrzeni, 2020)
The electronic writ-of-payment procedure makes an alternative to basic civil procedure. It was introduced into the Civil Procedure Code on 1 January 2010. It is provided for in respect of pecuniary claims pursued pursuant to Chapter 3, Section V of Title VII of Book VII of Part One, Book I of the Code of Civil Procedure. Electronic writ-of-payment proceedings have been introduced as separate proceedings in cases where the facts are not complicated and no evidence must be taken. This procedure is governed by the provisions on writ-of-payment proceedings with separations arising from Article 50528 - Article 50537 of the Code of Civil Procedure.